Radial oxygen loss by the cushion plant Eriocaulon schimperi prevents methane emissions from an East‐African mountain mire. (14th July 2017) - Dullo, B. W.; Grootjans, A. P.; Roelofs, J. G. M.; Senbeta, A. F.; Fritz, C.; Lamers, L. P. M.
Abstract: Groundwater‐fed fens are known sources of methane (CH4 ) emissions to the atmosphere, and these are known to be mediated by the vegetation. In a fen located in the Bale Mountains, Ethiopia, we assessed the effects of a cushion plant ( Eriocaulon schimperi) and a sedge ( Carex monostachya ) on rhizosphere biogeochemistry. Methane and CO2 concentrations and pH were measured in pore‐water at different depths in the profile. Redox potentials and NaCl‐extractable element concentrations were analysed in soil samples from sites dominated by either E. schimperii or C. monostachya . Nutrient and element concentration were analysed in plant tissues. At Carex ‐dominated sites, CH4 concentrations increased from 70 μmol·l −1 at a depth of 10 cm to 130 μmol·l −1 at a depth of 100 cm. CH4 concentrations at Eriocaulon ‐dominated sites were almost zero (<1 μmol·l −1 ) to a depth of 100 cm. Simultaneously, soil redox potentials and CO2 concentrations were higher at Eriocaulon ‐dominated sites, indicating a low potential for CH4 production and a high potential for CH4 oxidation. Eriocaulon schimperi displayed a root investment strategy to cope with the harsh environment, similar to the cushion plant Astelia pumila in Patagonian bogs. This strategy is characterised by high root/shoot ratios, high root porosity and density under high redox conditions. Both cushion plant species create an aerobic rhizosphere through radial oxygen loss from deep roots, which strongly reduce CH4 fluxes to the atmosphere.